Design of Automatic Switching Bio-Impedance Analysis (BIA) for Body Fat Measurement - Munawar A Riyadi; Achmad Ngaqib Muthouwali; Teguh Prakoso (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Bioelectrical impedance analysis (BIA) is one method of measuring body fat levels by distinguishing the fat mass and non-fat mass based on body composition assessment. This research designs a system to measure the body fat percentage by BIA method. The system is capable of measuring BIA with automatic switching between four different electrode schemes, i.e cross-sectional, hand-to-hand, hand-to-foot, and foot-to-foot. Two electrodes are to conduct current into the body, while other two electrodes are utilized to measure the voltage from the body. The alternating current is injected with frequency of 50 kHz. Automatic switch in the form of multiplexers and demultiplexers controls the sequence of BIA measurement methods. Microcontroller process the data and the result is displayed on LCD. A keypad is used to input related body parameters, i.e height, weight, age, and gender. The measurement tests shows that the BIA works as intended, while the comparison with commercial BIA reveals maximum relative error of 4.6 % and the highest standard deviation of 2.2%.